2016
DOI: 10.1002/smll.201603217
|View full text |Cite
|
Sign up to set email alerts
|

Direct‐Writing Multifunctional Perovskite Single Crystal Arrays by Inkjet Printing

Abstract: Perovskite single-crystalline microplate arrays are directly achieved in large scale by inkjet printing, which present high performance lasing property with quality factors up to 863 and RGB (red-green-blue) emission. This facile, nonlithographic method makes its promising applications on multi-integrated coherent light sources and other high-performance integrated optoelectronic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 36 publications
2
135
0
Order By: Relevance
“…In this section, recent developments of halide perovskite micro‐/nanostructures are discussed according to the structure and morphology dimensionality. The representative works over the past 5 years are summarized in Table 2 and Figure …”
Section: Different Dimensional Metal Halide Perovskites For Lasingmentioning
confidence: 99%
“…In this section, recent developments of halide perovskite micro‐/nanostructures are discussed according to the structure and morphology dimensionality. The representative works over the past 5 years are summarized in Table 2 and Figure …”
Section: Different Dimensional Metal Halide Perovskites For Lasingmentioning
confidence: 99%
“…In addition to substrate temperature, the wetting of the printed ink drops to the surface can be tuned, by controlling the adhesion, measured by the drop contact angle. Gu et al demonstrated, that the crystallite structure and wetting of the printed ink directly depends on the surface adhesion force, by manipulating the contact line . On high adhesion substrates, e.g., good wetting, the nucleation free energy is lowered and heterogeneous nucleation, as described in Section ., starts from multiple seed crystals within the deposited droplet .…”
Section: From Perovskite Ink To Printed Nanocrystals Wires and Thinmentioning
confidence: 99%
“…Green: MAPbBr 3 , blue: MAPbCl 2.4 Br 0.6 , and red: MAPbI 0.43 Br 2.57 . Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Inkjet‐printed Perovskite‐based Optoelectronicsmentioning
confidence: 99%
“…However, the solubility of halide perovskites in many common solvents (such as water, acetone, and alcohol) and their instability in ambient condition have impeded their development in conventional device fabrication. Although some fabrication methods for halide perovskite microplatelet arrays have been reported, it is still a great challenge and interesting to integrate various classes of perovskite films or single crystals into one chip or read out integrated circuits. Especially, it is important to integrate the 2D perovskite materials into different device structures to fully uncover their electronic and optoelectronic properties.…”
Section: Challenges and Outlookmentioning
confidence: 99%